Patterns of drug-related problems and the services provided to optimize drug therapy in the community pharmacy setting - Anan S. Jarab; Walid Al-Qerem; Karem H. Alzoubi; Mohammad Tharf; Shrouq Abu Heshmeh; Ahmad Al-Azayzih; Tareq L. Mukattash; Amal Akour; Yazid N Al Hamarneh (Saudi Pharmaceutical Journal, 2023)
Introduction: Drug-related problems (DRPs) are events or circumstances involving drug therapy that actually or potentially interferes with desired health outcomes. Objectives: To assess community pharmacists’ knowledge and practice regarding DRP-reduction services, as well as the barriers and factors associated with decreased provision of these services. Methods: This cross-sectional study utilized a validated questionnaire to assess pharmacists’ knowledge, practice, and barriers to the provision of DRP-reduction services in the community pharmacy setting. Binary regression model was used to assess the variables associated with the practice of DRP-reduction services. Results: A total of 412 pharmacists participated in the study. The pharmacists demonstrated strong knowledge but inadequate practice of DRP-reduction services. The most reported DRPs were inappropriate combination of drugs, or drugs and herbal medications, or drugs and dietary supplements (52.4%), patients’ inability to understand instructions properly (46.1%), inappropriate drug according to guidelines (43.7%), and too high dose (40.3%). The most common barriers to these services were increased workload (60.5%), limited time (53.2%), and lack of good communication skills (49.8%). The presence of a counselling area in the pharmacy increased the practice of DRP-reduction services (OR: 3.532, 95%Cl: 2.010–5.590, P < 0.001), while increased weekly working hours (OR: 0.966, 95%Cl: 0.947–0.986), P < 0.01) and serving < 10 patients daily (OR = 0.208, 95%Cl: 0.072–0.601, P < 0.01) decreased it. Conclusions: Community pharmacists’ practice of DRP-reduction services showed a scope for improvement. Future pharmaceutical care initiatives should increase the number of personnel working in the pharmacy and provide them with opportunities for continued education and training in order to improve the provision of DRP services and optimize patients’ outcomes.